Revisiting U.K. Delay and Disruption Protocol: Distinguished Features for Contract Drafting - Chong, Heap Yih; Tan, C.; Munir, O. (ASCE, 2014)
The Delay and Disruption Protocol was published by the Society of Construction Law in 2002 in the United Kingdom. It has been well received by construction professionals for its guidance in solving delay and disruption issues. This research attempts (1) to compare the Protocol’s core features with the existing references for the contracting parties and (2) to determine the feasible use of the Protocol’s distinguished features into the Malaysian construction industry as a case study. The distinguishing features were identified after reviewing and comparing the local contract forms and the Protocol. Subsequently, the questionnaire survey was carried out with local developers, contractors, and consultants based on an inductive reasoning approach. Statistical and variance analyses were conducted to determine the acceptance level of the Protocol’s features. The results show that most of the features were agreed to by the respondents; for instance, the guidelines on float identification, concurrency identification, proper procedures on work program, and so on. The findings render useful information for future contract drafting by incorporating the guidelines into local contract forms, particularly for commonwealth countries.